Penambahan Nilai Ekonomi Jajanan Tradisional Umkm “Bu Sie” Melalui Logo Produk Untuk Menunjang Sustainable Income - Dhita Firellya Yuniar; Richo Diana Aviyanti (BADAN PENERBIT STIEPARI PRESS, 2024)
The logo is related to the product brand which can be a competitive advantage for MSMEs. A logo can become a business identity and visual attraction for traditional snack MSME products. The aim of this activity is to strengthen business identity through logo design training and obtain sustainable results. The method for implementing this service is socialization and design practice tutorials for Mrs. Sie's traditional snack business. The results of this service activity are giving product logos to Bu Sie's traditional snacks, increasing sales turnover, strengthening business identity and also as promotional media. MSMEs receive education about logo design and how to make them using tools commonly used in printing, thereby facilitating the production process while reducing the cost of printing logo stickers.